Pedagogical Practices for Fostering Agentic Engagement in Experiential Learning: A Systematic Literature Review - Hidayah, Nurul; Utari, Rahmania (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study systematically synthesizes international research on pedagogical practices that foster agentic engagement in experiential learning contexts. Agentic engagement emphasizes learners’ proactive participation in shaping learning processes through initiative, decision-making, and meaningful interaction, making it a key element of student-centered pedagogy. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines using the Scopus database as the primary source of literature. The initial search identified 622 publications, which were screened through identification, eligibility assessment, and full-text review, resulting in 10 studies that met the inclusion criteria. The thematic synthesis revealed four major pedagogical dimensions that support agentic engagement: (1) learner-related factors, including self-efficacy, intrinsic motivation, and perceived competence; (2) instructional support through autonomy-supportive teaching, dialogic feedback, and student voice; (3) experiential learning design characterized by collaboration, problem-solving, co-creation, and opportunities for decision-making; and (4) pedagogical outcomes reflected in enhanced leadership, communication, resilience, self-regulation, and sustained participation. These findings indicate that agentic engagement is strengthened through pedagogical practices that position learners as active contributors rather than passive recipients of instruction. The review highlights the potential of experiential learning environments, including extracurricular activities such as scouting, to operationalize these practices within broader educational settings. The findings provide theoretical and practical implications for designing learner-centered pedagogical environments and offer directions for future research on technology-enhanced experiential learning that supports agentic engagement.